Implementing climate change research at universities: barriers, potential and actions - Leal Filho, Walter (2020)
Many universities around the world have been active centres of climate change research. However, there are a number of barriers to climate change research, stemming both from the nature of there search and the structure of institutions.This paper offers an overview of the barriers which hinder the handling of matters related to climate change at institutions of higher education (IHEs), and reports on an empirical study to investigate these barriers using a global survey of higher education institutions. It concludes by proposing some steps which could be followed with a view to making climate change more present and effective in university research and teaching. These include changing approaches to research, outreach and teaching to better support action on climate change.